Vegetation Characteristics of The Maleo Bird (Macrochepalon maleo) Habitat at Natural Tourism Park of Towuti Lake, South Sulawesi - Hadijah , Hadijah Azis Karim; Nardy, Nardy Noerman Najib; Nada , Nada Sofyan (Jurnal Wasian, 2022)
Maleo birds (Macrocephalon maleo) generally have habitats in forests near hot springs, but in East Luwu Regency their habitat is found on the shores of Lake Towuti. It is suspected that the habitat of maleo birds at the site has different characteristics. This study aims to identify the vegetation characteristics of maleo bird habitat in the sleeping area and tread where to lay eggs. Vegetation analysis was carried out by purposive sampling with a plot size of 20 m x 20 m in the sleeping area, and 5 m x 5 m in the laying site where the egg-laying was located. The data collected are the name of the type, diameter, the individual number of trees, poles, stakes, and seedlings. The results showed that in sleeping areas, macadamia hildebrandii trees have the highest INP values. Macadamia hildebrandii fruit is thought to be one of [1]the feeds for Maleo birds. In egg-laying habitats, Imperata cylindrica has the highest INP compared to other types. On the tread of the egg-laying nests can be seen maleo birds eating grass grains. There are differences in ecological index [2]values found in sleeping habitats, namely H'= 2.24 (medium), Dmg= 3.02 (low), and E= 0.81 (high). However, in egg-laying habitats, the Ecological Index values found were H'= 0.62 (low), Dmg= 0.93 (low) and E= 0.30 (low). The discovery of maleo birds in Lake Towuti TWA makes the area one of the remaining in situ habitats in South Sulawesi and can be a consideration for the government to maintain and preserve it.